ETNOBOTANY OF TRADITIONAL MEDICINE PLANTS OF MANDAILING TRIBE IN THE SIMPANG TALAP RIVER FLOW REGION, RANTO BAEK DISTRICT, MANDAILING REGENCY - Ofy Asyma Matondang; Dina Handayani (JBIO: jurnal biosains (the journal of biosciences), 2022)
Documentation of the use of medicinal plants is a race against time. This traditional medical science is not documented, only conveyed orally, it is attractive to the elderly and less attractive to teenagers, causing this knowledge to be left behind and lost in one generation. This study aims to publish and document belief systems, utilization practices, local knowledge and cultural importance values of traditional medicinal plant species of the Mandailing Tribe. Location The research was conducted in Manisak Village, Ranto Baek District, Mandailing Natal Regency, which was held from December 2021 to March 202. Data was collected through semi-structured interviews, participatory observation, documentation, Collection of plant samples and the manufacture of herbarium. The data were analyzed descriptively qualitatively and quantitatively. The results showed that the Mandailing people used 44 species of medicinal plants which were included in 30 families. The highest family was Zingiberaceae 4% while the lowest family was Rutaceae 1%. The highest habitus of herb and the least habitus was liana. The practice of using plants by the Mandailing Tribe begins with meeting the datu, providing materials, materials in the form of plants obtained from the advice of the datu or parents who understand the pulungan of medicinal plants, the method of processing is mostly boiled and the method of use is mostly by drinking. Eme (Oriza sativa) with an ICS value of 71, its use is as a medicinal ingredient, a staple food ingredient that has no substitute, and traditional ritual events (mythology). Keywords: Ethnobotany, Traditional Medicine, Mandailing Tribe Belief System, utilization practices, local knowledge, Values of cultural importanc.